The Effect of Scaffolding Method on Self-Regulation, Retention, and Comprehension of Sixth-Grade Science - Mirasi, Robab; Mesrabadi, Javad; Aghdasi, Ali Naghi (Assessment and Practice in Educational Sciences, 2025)
Human life is fundamentally grounded in educational processes, and transformations in learning are inseparably linked to individuals’ social, cultural, and occupational advancement. Therefore, the application of the scaffolding method in teaching and learning can serve as an influential factor in learners’ educational outcomes. The aim of the present study was to examine the effect of instructional scaffolding, compared with traditional teaching, on self-regulation, retention, and comprehension in the subject of experimental sciences. This research employed a quasi-experimental design with pretest-posttest and both experimental and control groups. The participants were assigned to two groups (the experimental group receiving instructional scaffolding and the control group). They were evaluated using the Self-Regulation Questionnaire developed by Bouffard (1995) and teacher-made tests of retention and comprehension administered before and after the intervention. The experimental group received eight sessions of instruction through educational packages designed and optimized by a university lecturer specializing in educational psychology and instructional design, whereas the control group received traditional teaching. The traditional teaching consisted of instruction delivered by the classroom teacher without any research intervention, specific strategies, or educational packages. The statistical population consisted of sixth-grade female students in Marand city, and the sampling method was convenience sampling. The results of covariance analysis indicated that scaffolding-based instruction had a significant effect on students’ self-regulation, retention, and comprehension. These findings suggest that scaffolding as an instructional method can be effectively employed to improve self-regulation, retention, and comprehension among students.